(untitled) - Widdowson, H. G. (Oxford, 1991)
This book provides a timely critical review of the most prominent issues in language teaching today. Part 1 presents the case for the relevance of theoretical enquiry to classroom practice. Parts 2 and 3 serve to demonstrate this relevance by showing how different perspective on linguistic description lead to different approaches to the teaching of language.
Keywords: Language and languages; Foreign speakers,Study and teaching